The message of our Prophet Muhammad (may God’s prayers and peace be upon him and his family) and its evidence and refutation of abuse in the light of the contemporary scientific method (Journal of Misan Researches, 2022)
This study aims to clarify the message of the Noble Prophet Muhammad bin Abdullah (PBUH) and the evidence for its proof in the two parts Al-Naqali.     We have also worked to prove the scientific views of the theologians, hadith scholars and thinkers, in refuting the flimsy suspicions that are raised to undermine the prophecy of the Prophet  according to the system of the contemporary scientific method, which is consistent with the aspirations of the era in style and subtraction, through scientific methods with clear meanings, and avoiding stiffness and fanaticism in subtraction. , through the moderate scientific evidence for the blind.      Whoever wants to destroy the will of generations according to weak foundations, he must first answer the questions of the Holy Qur’an in preserving the prophetic message, and the inability of others to come, if they were able even if only one verse, they were not able to do so.      So, it has been proven through conclusive evidence that the message that the Prophet Muhammad (PBUH) brought is a heavenly message, which God Almighty wanted to be a conclusion to the prophetic messages and to make the bearer of the seal of prophecy and message. All of this has been proven by sensory and non-sensory miracles, in addition to that. All of the Prophet Muhammad (PBUH) was called Truthful and Trustworthy before his mission, so everyone who knew him and witnessed him believed in him sincerely with heart and tongue. Calculating the weakness of other Muslims in taking their rights with falsehood and force, to lord it over them